1974
DOI: 10.1002/hlca.19740570629
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthese der Cytochalasane. Teil II Die Grundbausteine von Cytochalasin D

Abstract: A number of potential 14C‐ and 3H‐labelled precursors were fed to growing cultures of Zygosporium masonii after the rate of formation of cytochalasin D had been measured. By chemical degradation of [14C]‐ and [3H, 14C]‐cytochalasin D the distribution of the radioactivity originating from incorporated [4′‐3H, U‐14C]‐L‐phenylalanine and [CH3‐14C]‐L‐methionine was determinated. The results demonstrate that the building blocks of cytochalasin D are 1 unit of pheylalanine, 3 units of methionine and acetate units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…One additional acetyl group is introduced into the carbon backbone, as well as three methionine-derived C 1 groups: one methylene group at C-12 and two methyl groups at C-16 and C-18. 103 Interestingly, both DL-and L-phenylalanine were equally well incorporated into cytochalasin D due to a rapid equilibrium of D-and L-phenylalanines via phenylpyruvic acid. However, the L-enantiomer was shown to be the primary precursor.…”
Section: Isotope Labelling Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…One additional acetyl group is introduced into the carbon backbone, as well as three methionine-derived C 1 groups: one methylene group at C-12 and two methyl groups at C-16 and C-18. 103 Interestingly, both DL-and L-phenylalanine were equally well incorporated into cytochalasin D due to a rapid equilibrium of D-and L-phenylalanines via phenylpyruvic acid. However, the L-enantiomer was shown to be the primary precursor.…”
Section: Isotope Labelling Experimentsmentioning
confidence: 99%
“…1) confirmed the previous results. [103][104][105][106] Tamm and co-workers showed that this metabolite originates from one phenylalanine unit fused to an acetate/malonate-derived octaketide chain without loss of the carboxyl group. One additional acetyl group is introduced into the carbon backbone, as well as three methionine-derived C 1 groups: one methylene group at C-12 and two methyl groups at C-16 and C-18.…”
Section: Isotope Labelling Experimentsmentioning
confidence: 99%
“…In general, cytochalasans are characterized by a highly substituted perhydro-isoindolone moiety to which typically a macrocyclic ring is fused. Isotope labeling experiments and biosynthesis studies have revealed that biosynthetic pathways of cytochalasans involve the formation of an acetyl- and methionine-derived polyketide chain and the attachment of an amino acid such as phenylalanine, leucine, or tryptophan 15 16 17 18 19 . Aspochalasins are a subgroup of cytochalasans with leucine as the original precursor.…”
mentioning
confidence: 99%
“…Since related work in this laboratory has concentrated on the physiological effects of CA, the need has arisen to label this congener. The biosynthetic pathway leading to the cytochalasin backbone has been demonstrated to utilize a phenylalanine-acetate-polymalonate pathway (3). Biosynthetic experiments utilizing labeled phenylalanine in the enriched medium resulted in a 2 to 4% incorporation of labeled [14C]or [3H]-L-phenylalanine into CB.…”
Section: Discussionmentioning
confidence: 99%